2016
DOI: 10.1039/c5ra27526a
|View full text |Cite
|
Sign up to set email alerts
|

Promising Ni/Al-SBA-15 catalysts for hydrodeoxygenation of dibenzofuran into fuel grade hydrocarbons: synergetic effect of Ni and Al-SBA-15 support

Abstract: First time application of Al-SBA-15 supported Ni catalysts for hydrodeoxygenation of dibenzofuran to hydrocarbons was investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…However, the contribution of Ni species more strongly interacting with the support observed for Zr-modified Ni/AlSBA-15 was considerably higher than that noted for the unmodified mesoporous catalyst. This was consistent with previous studies, which demonstrated that the presence of zirconium enhanced the strength of the interaction between the support and nickel clusters. ,, …”
Section: Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the contribution of Ni species more strongly interacting with the support observed for Zr-modified Ni/AlSBA-15 was considerably higher than that noted for the unmodified mesoporous catalyst. This was consistent with previous studies, which demonstrated that the presence of zirconium enhanced the strength of the interaction between the support and nickel clusters. ,, …”
Section: Results and Discussionsupporting
confidence: 93%
“…In this case, two reduction peaks with the maxima at 300 and 570 °C were noticed. The first of them can be ascribed to nickel oxide with the limited contact with the support, while the second can be attributed to NiO strongly interacting with the mesoporous material, as previously reported in the literature. , …”
Section: Results and Discussionsupporting
confidence: 68%
“…Catalytic hydrodeoxygenation (HDO) of lignin oil is a promising strategy to reduce the amount of oxygen, resulting into a high-quality bio-oil that can be efficiently upgraded to compatible transportation fuels. [189][190][191][192] Co-Pyrolysis of cellulose and cobalt nitrate under NH 3 atmosphere was performed to prepare novel magnetic N-doped carbon supported cobalt nitride catalysts (CoN x @NC). 193 Their catalytic efficiency for HDO of lignin-derived phenols was subsequently tested.…”
Section: Biomass-derived Carbon Catalystsmentioning
confidence: 99%
“…In our previous work, the hydrodeoxygenation products of DBF were obtained and the hydrogenation pathway (HYD) was discussed in detail. Considerable research has been focused on the hydrodeoxygenation of DBF to fuels via the HYD pathway over acid catalysts. Only a few studies of the DBF hydrogenolysis to OPP have been reported in the literature, in which the selectivity for OPP reached 73% and the yield was just 16.8% over carbon supported Pd catalyst. As a consequence, C–O bond hydrogenolysis has been extensively studied over the past decade .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, C–O bond hydrogenolysis has been extensively studied over the past decade . Various metals have been used as the active components, such as Ru, Pt, , Pd, Rh, Ni, , Cu, , Fe, Au, W, and Co, and important progress has been made toward the cleavage of the C–O bond. In particular, the noble metals, Pt, Pd, Ru, and Rh, have attracted considerable attention because of their high hydrogenolysis activity.…”
Section: Introductionmentioning
confidence: 99%